Impact of Price-Adjustments Costs on Integration of Pricing and Production Planning of Multiple-Products - Mardaneh, Elham; Caccetta, Louis (Springer Verlag, 2014)
Joint pricing and production decisions are crucial to the competitiveness of a manufacturing company. A common assumption in coordination of pricing and production planning decisions is that the price-adjustments are costless. However, those costs are not negligible, as they may take up a significant part of the firms’ reported profit. In this paper, we consider multi-product multi-period production planning systems with costly price-adjustments. A capacitated setting is investigated and a demand-based model where the demand is a function of the price is introduced. Effective computational models will be developed for both deterministic and stochastic price dependent demand. Both fixed and variable price-adjustment costs will be considered. The aim of the paper is to utilize the existing commercial packages for optimization and compare the effectiveness of various models for addressing realistic size problems. In the case of uncertain demand function, we focus on an additive demand model for which the underlying random variable is normally distributed. By using a chance constrained programming approach, we show that the model is still solvable for realistic size problems. We also develop a robust optimization model to fit in a scenario-based demand function. Computational results on a range of test problems support the effectiveness of our models.